Long-term outcomes after transcatheter aortic valve replacement in nonagenarians: a multicenter age-based analysis. Issue 3 (29th March 2021) - Costa, Giuliano; Valvo, Roberto; Fiorina, Claudia; Adamo, Marianna; Giannini, Cristina; Testa, Luca; Bruschi, Giuseppe; Poli, Arnaldo; De Felice, Francesco; Montorfano, Matteo; Maffeo, Diego; Iadanza, Alessandro; et al.
Abstract : Aim: To assess the outcome of nonagenarians patients receiving transcatheter aortic valve replacement (TAVR). Methods: We aimed to stratify the overall population from an Italian, multicenter, observational project including a total of 3792 consecutive patients who underwent TAVR with CoreValve and Evolut R/PRO devices between April 2009 and October 2018, into four groups according to their age class (≥90 vs. 80–89 years vs. 70–79 vs. <70 years) and to compare outcomes up to 4 years after TAVR. Results: At 4 years, survival estimates showed no difference in terms of overall survival [Kaplan–Meier estimates (KM est.) 49.9 vs. 58.1% vs. 57.0 vs. 69.3%; P logrank  = 0.28] among the four groups. After 2 years from the procedure, landmark analysis showed an age-based difference in overall survival (KM est. 63.8 vs. 75.0% vs. 75.1 vs. 88.7%; P logrank  = 0.025) but no difference in terms of survival from cardiovascular death (KM est. 87.8 vs. 87.4% vs. 86.1 vs. 96.1%; P logrank  = 0.43). Finally, age itself was not correlated with overall mortality at 4 years (hazard ratio 1.06, 95% confidence interval 0.86–1.30, P  = 0.591). Conclusion: TAVR with self-expanding CoreValve and Evolut prostheses was demonstrated to have good long-term outcomes, regardless of the patient's age. At 4 years, no difference in overall mortality was reported among age-based groups, while a higher overall mortality was reported in nonagenarians after 2 years from the procedure. TAVR showed good long-term outcomes even in nonagenarian patients, and it could be the therapy of choice for selected elderly patients.